(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
We come from different cultures but what we share creates the basis for our mutual understanding. The other not understanding is rarely a problem, if there is openness, genuine engagement, an underlying deep respect for difference and a genuine intent to understand - all of which are often conveyed non-verbally.